A strategic analysis of diwannie layer cakes / Suudi Arof … [et al.] - Arof, Suudi; Jahet, Dihem (2015)
The purpose of this study is to conduct a strategic analysis on Diwannie Layer Cakes, a product of Wannie Enterprise, a producer of the renowned Sarawak layer cake since 30 years ago. The Sarawak layer cake is very famous, and has become a must-buy product for tourists visiting the state, or their visit is considered incomplete if they return home without buying the Sarawak layer cake. This has contributed to the growth of the Sarawak layer cake industry and attracting more producers entering the business making it now more competitive.